Agreement of implantable collamer lens sizes using parameters from different devices - Nonpassopon M. (2023)
Objective To assess agreement and repeatability of white-to-white (WTW) and anterior chamber depth (ACD), and agreement of implantable collamer lens (ICL) size using these measurements from different devices. Methods and analysis A retrospective review of 83 eyes with ICL implantation (42 patients) was conducted. The agreement of WTW (measured with WaveLight Topolyzer and Orbscan IIz) and ACD (measured with WaveLight Oculyzer and Orbscan IIz) was analysed. Correlation of ICL sizes and difference of eyes with unacceptable vaults between two data sets (WaveLight platform; Topolyzer and Oculyzer and Orbscan IIz) were assessed. Results Average WTW measured by Orbscan IIz and Topolyzer demonstrated good agreement (P 0.884) with low systematic bias (-0.03±0.1 mm) and narrow 95% limits of agreement (LoA) of -0.28 to 0.22. Average ACD measured by Orbscan IIz and Oculyzer also showed good agreement (P 0.903) with low systematic bias (-0.04±0.1 mm) and relatively narrow 95% LoA (0.2 to 0.12). ICL size selected according to two data sets showed moderate to strong level of agreement (Kappa=0.81). There was a statistically significant difference (p<0.001) in the proportion of eyes with unacceptable postoperative vaults when using the Wavelight platform data set (five eyes, 6.02%) and the Orbscan IIz data set (12 eyes, 14.46%). Conclusion Although the agreement of WTW and ACD between devices was good, there was a significant difference in proportion of eyes with unacceptable postoperative vaults when using two data sets. Therefore, Topolyzer and Oculyzer might not be suitable for operating interchangeably with Orbscan IIz for ICL size selection.